Analysis of Healthy Latrine Ownership Factors in the Coastal Area of Lapulu Village, Kendari City - Sitti Marya Ulva; Sinar Jannah (MIRACLE Journal Of Public Health, 2021)
The percentage of families in Lapulu Village that had healthy latrines was 64,84% who met the health requirements and 35,16% who did not meet the health requirements in 2019. This shows that the ownership of healthy latrines is still lower than the national achievement. This study aims to determine the factors associated with low ownership of healthy latrines in the coastal areas of Lapulu Village, Kendari City. The research design was observational, with a cross-sectional approach. The population in this study was 437 respondents, while the study sample was 209 respondents. The sampling technique used was proportional random sampling technique. The analysis were performed using the Chi-Square test. The results of statistical tests with chi-square obtained the value of land availability (p-value=0,000), knowledge (p-value=0,031), and income (p-value=0,000). It can be concluded that there is a relationship between land availability, knowledge, and income levels associated with low ownership of healthy latrines in the tidal area of ​​Lapulu Village, Kendari City. Therefore, it is hoped that the community and local government will establish this inter sector collaboration with related agencies to increase community ownership of healthy latrines.